Agriculture extensification and associated socio-ecological trade-offs in smallholder farming systems of Zambia - Masikati, Patricia; Sisito, G.; Chipatela, F.; Tembo, H.; Winowiecki, Leigh Ann (Informa UK Limited, 2021)
One of the main drivers of deforestation in Zambia is the expansion of agricultural land for increasing production areas and for shift cultivation due to poor crop management practices. Land expansion was also echoed by farmers in Northwestern province as they aim to increase yield via land expansion. It was therefore important to understand possible associated socio-ecological trade-offs in agricultural extensification and identify pathways to improve ecosystem services delivery and reduce trade-offs. We used the Tradeoff Analysis model for Multi-Dimensional (TOA-MD) and Agricultural Production Systems Simulator (APSIM) to assess trade-offs in both current and future farming systems under extensification (CP) and sustainable agriculture intensification (SAI). Thirty-year simulations showed that agricultural extensification will lead to loss of soil organic carbon) and total soil nitrogen of about 23% and 22%, respectively leading to yield reductions of about 35% and increased poverty levels. However, SAI approach results showed that poverty can be reduced by about 20% for farmers with land holdings of 3 ha while those with 2 and 5 ha can be reduced by 10% and 5% respectively. The proposed SAI has potential to reduce poverty, maintain good current and future crop production, and potentially aid farmers to reduce opening new fields.